2004
DOI: 10.1037/0894-4105.18.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Reading and Phonological Awareness in Williams Syndrome.

Abstract: This article describes the relationship between reading, phonological awareness abilities (PA), and intelligence in a group of 16 individuals with Williams syndrome (WS) and in a group of 16 typically developing children, matched for mental age. The individuals with WS were impaired in passage comprehension, in some areas of PA investigated (syllable deletion and rhyme detection), and in nonword reading accuracy, a measure of grapheme-phoneme conversion. This latter finding is relevant, considering that in Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0
14

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 78 publications
8
42
0
14
Order By: Relevance
“…The absence of a contextuality effect even in the case of low frequency words supports the idea that Elisa applies a whole-word lexical reading procedure to all kinds of stimuli. Our findings are consistent with those of Menghini et al (2004), suggesting that WS individuals have difficulties in grapheme-phoneme conversion as demonstrated by their poor performance in nonword reading. Consistent with this view, Majerus (2004) found that WS individuals have poor performance in some meta-phonological awareness tasks (specifically those involving nonwords) suggesting qualitatively different phonological processing in WS.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The absence of a contextuality effect even in the case of low frequency words supports the idea that Elisa applies a whole-word lexical reading procedure to all kinds of stimuli. Our findings are consistent with those of Menghini et al (2004), suggesting that WS individuals have difficulties in grapheme-phoneme conversion as demonstrated by their poor performance in nonword reading. Consistent with this view, Majerus (2004) found that WS individuals have poor performance in some meta-phonological awareness tasks (specifically those involving nonwords) suggesting qualitatively different phonological processing in WS.…”
Section: Discussionsupporting
confidence: 94%
“…However, in nonword reading WS performance was worse than controls', suggesting impairments in grapheme-to-phoneme (g-p) decoding with relatively spared whole-word procedure. To our best knowledge, Temple (2003) and Menghini et al (2004) are the only studies in which lexical and nonlexical reading of WS have been investigated, and both have led to converging conclusions.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Studies on phonological awareness in individuals with WS have shown that the phonological process plays an important role for the acquisition of reading skills [15][16][17] . Phonological awareness is an intentional reflection on speech that has different levels, i.e., the segmentation of spoken language can happen in different units: a sentence can be segmented in words, words can be segmented in syllables…”
Section: Support Sources: Capes Mackpesquisamentioning
confidence: 99%